P157 Hiatus hernia is highly prevalent in idiopathic pulmonary fibrosis and impacts disease progression. (December 2018) - Desai, SR; Mackintosh, JA; Chua, F; Renzoni, E; Kouranos, V; Margaritopoulos, G; Kokosi, M; Maher, TM; Wells, AU; Molyneaux, PL; Kumar, S; George, PM
Abstract : Background: Hiatus hernia is common but the influence on outcomes in patients with idiopathic pulmonary fibrosis (IPF) remains controversial. In a recent phase 2 randomised controlled trial of IPF patients, it has been suggested that laparoscopic anti-reflux surgery might improve outcomes. The aim of this study was to evaluate the prevalence of hiatus hernia in patients with IPF and the impact on outcomes. Methods: A cohort of patients with a multi-disciplinary diagnosis of IPF underwent retrospective review for the presence of hiatus hernias on thoracic CT. Serial lung function and mortality were compared in those with and without hiatus hernia. Results: CT scans from 70 IPF patients (82.9% male, mean age 67.9±8.1 years) were analysed. All patients were prescribed anti-fibrotic therapy. Co-existent pleuroparenchymal fibroelastosis (PPFE) was present in 12/70 (17.1%). Serial lung function was performed a mean of 11.1±5.4 months apart. Mean baseline FVC%pred was 68.9%±12.2% and TLco%pred 38.2%±12.2%. Mean FVC decline was 194 mL ±377 mL (6.8%±12.8%) and mean TLco decline was 15.0%±22.4%. Hiatus hernia was present in 30/70 (42.9%), the majority of which were graded as small (20/30 (66.6%)). There was no difference in the baseline lung function between those with and without a hiatus hernia. Mean decline in FVC was significantly greater in IPF patients with a hiatus hernia (−298 mL ±451 mL) than those without (−114 mL ±289 mL) (p=0.02). Larger hernia size was not associated with greater FVC decline. PPFE was no more prevalent in those with a hiatus hernia (p=0.927). Eighteen patients (21.8%) had evidence of oesophageal dilatation or food debris, with no association with lung function decline. Overall mortality was 44/70 (62.9%) with a median survival in those with and without hiatus hernia of 31 and 44 months respectively (p=0.7). Conclusion: Hiatus hernia is present in over 40% of patients with IPF, a much higher rate than is reported in other chronic lung diseases. The presence of hiatus hernia is associated with IPF disease progression as measured by FVC decline. This supports further prospective studies including the functional assessment of hiatus hernia in IPF and response to interventional reflux therapies.